Direct growth of orthorhombic Hf0.5Zr0.5O2 thin films for hysteresis-free MoS2 negative capacitance field-effect transistors - Hae Won Cho; Pavan Pujar; Minsu Choi; Seunghun Kang; Seongin Hong; Junwoo Park; Seungho Baek; Yunseok Kim; Jaichan Lee; Sunkook Kim (npj 2D Materials and Applications, 2021)
Abstract Herein, the direct growth of polar orthorhombic phase in Hf0.5Zr0.5O2 (HZO) thin films is reported using Pulsed Laser Deposition (PLD). The growth of HZO onto a preheated (700 °C) silicon substrate mimics the rapid thermal annealing, which allows the formation of smaller crystallites (~9.7 nm) with large surface energy leading to the stabilization of metastable orthorhombic phase. Unlike atomic layer deposition (ALD) of HZO, PLD is more advantageous for depositing highly crystalline thin films through optimized parameters, such as laser fluence and background gas pressure. Further, the PLD-HZO is integrated with HfO2 dielectric and the resulting gate stacks have been used in the bottom gate FET architecture-‘Si//PLD-HZO/HfO2/MoS2//Ti/Au’. The NCFETs have yielded a sub-thermionic subthreshold swing (SS for  = 33.03 ± 8.7 mV/dec. and SS rev  = 36.4 ± 7.7 mV/dec.) and a negligible hysteresis (~28 mV), which is capable in realizing low power integrated digital/analog circuits.